Strengthening Service Performance in Indonesian Public Sector - Aninda Rahmasari; Maria Grace Herlina; Dicky Hida Syahchari (Binus Business Review, 2022)
Quality service has become increasingly important in the public sector. Government services and their quality requirements are developing in response to changes in customers’ needs and expectations. The primary objective of the research was to strengthen public sector performance. It used a sustainable service view by examining professional public service as a mediating variable of service-oriented competence, socio-emotional ability, and workplace spirituality on sustainable service performance in Indonesia. A structured questionnaire was sent to public sector employees using a non-probability sampling method with convenience sampling. The Structural Equation Modeling (SEM) was used to test the research hypotheses using the SmartPLS version 3.2.9. After assessing the measurement model, the results show that service-oriented competence, socio-emotional ability, and workplace spirituality affect sustainable service performance significantly. Furthermore, the professional public service strengthens the relationship of service-oriented competence, socio-emotional ability, and workplace spirituality on sustainable service performance. It also implies a novel result by demonstrating that professional public service can mediate service-oriented competence, socio-emotional ability, and workplace spirituality toward sustainable service performance. Although hard skills are essential for knowledge of service-oriented competence, the research findings show that soft skills, particularly socio-emotional ability, will assure the public sector’s sustainable service performance. Therefore, soft skill development is very important for enhancing socio-emotional abilities.